AB0173 Predict of rheumatoid arthritis one year after treatment with t2t protocol with the reference of boolean-based evaluation and total sharp score. (23rd January 2014) - Yoshii, I.; Chijiwa, T.
Abstract : Background: Treatment according to T2T recommendation is now spreading worldwide for tight control of rheumatoid arthritis (RA) disease activity. This protocol aims prevent of joint destruction that results in ADL maintenance in a long term. Almost rheumatologist agrees with it, however, many monitoring indices were recommended for the evaluation of disease activity control, and it is well known that sustain of tight disease activity control is difficult. Objectives: We have compared disease activity control indices such as SDAI, DAS28, Boolean, and derived evaluations whether these indices are reproducible for prediction of disease activity and ADL maintenance. Methods: In our institute, all rheumatoid arthritis patients were treated with identical treatment protocol based of T2T recommendations since August 2010. Patient's disease activity is monitored with CDAI, SDAI, DA28, and Boolean evaluations, patient's pain score, and Health Assessment Questionnaire (HAQ-DI) and followed up every another month until clinical remission is fulfilled. After fulfillment, their follow-up period is changed to 2 or 3 months interval. Joint structure is evaluated with modified total Sharp score (mTSS) at first attendance, at the time of protocol change, at latest, every another year. 386 patients were followed up for more than 2 years. These patients have been picked up in this study. Every patient's disease activity indices such as time average DAS28, time average SDAI, DAS28 remission ratio, SDAI remission ratio, Boolean remission ratio, average HAQ-DI, were calculated for every year. Patients were classified into groups according to levels of each index in first year. Probability of clinical results in the second year with use of such indices were calculated and every another group was compared statistically. These indices were evaluated as parameter for prediction of clinical results in the second year statistically with Chi square test. Results: The statistically most significant index for prediction of clinical result on the second year was Boolean evaluation. Every patient who has more than 75% probability of Boolean remission ratio, demonstrated 77.42% sensitivity of Boolean remission in the second year, while specificity was 85.23%. These patients' average probability of HAQ-DI with no more than 0.25 in the second year was 96.77%, while specificity was 34.09%. However, if mTSS is added to collateral condition, more stringent result is demonstrated. In Group1 patients, who has no more than 50 points in mTSS demonstrated 100% probability of no more than 0.25 in HAQ-DI in the second year, while specificity was 41.33%. Other indices such as CDAI, SDAI and DAS28 also showed significant difference for each probability group in the second year. However, no other indices demonstrated such significant evidence like Boolean evaluation. Conclusions: These results suggested the importance of tight disease activity control in early stage for RA treatment. Boolean evaluation is valuable index for prediction of RA clinical course. The more Boolean remission achieves in first year, the more probability of Boolean remission and HAQ-DI remission in the second year is predicted. We should apply this index more often in clinical practice. Disclosure of Interest: None Declared